VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Talent Identification (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-112 General and special physical fitness levels in young football players P-113 Talent identification in soccer players aged 10-12 years P-114 Characteristics of selected and non-selected elite junior Australian footballers P-115 Impact of playing level on skill performance in early pubescent Irish soccer players P-116 Possible predictor of talent identification of professional soccer players P-117 Heart rate and match analysis of Finnish junior football players P-118 Career development of youth football players in J-League Academy: Focus on occupational identity